Autoridade docente em crise - Costa, Luciana Santos Andrade (2021)
This work, part of the State, Politics and History of Education research line, aims to a) carry out the theoretical study of the concept of authority to think about teaching authority; b) produce a study of the bibliographic production on the theme of teaching authority; c) list and discuss themes associated with the teaching authority that are most present in the selected bibliography production on the teaching authority and respective educational crisis. The methodological path involved the selection of some authors with a focus on the theme of authority and teaching authority followed by a bibliographical study based on the survey of published studies on the subject. These studies were published between 2000 and 2020 on three platforms, namely: 1) Theses and dissertations database from the Coordination for the Impro-vement of Higher Education Personnel (CAPES); 2) database of articles from the Scielo platform; 3) database of the National Meetings of the National Association for Graduate Studies and Research in Education (ANPEd), specifically in the Working Group GT07 Education for Children from 0 to 6 years. The text presents the main reflections about the works found, making a synthesis of the relation of the contributions of these works. Among the results we can say that the crisis of teaching authority is related to the crisis in education. This, in turn, is part of a multifactorial set that in-volves features of modern psychology, pragmatism and the capitalist mode of production that translates, for example, into educational politicians.